Human Capital Strategies to Address Artificial Intelligence Challenges in the Contemporary Work Environment - Ade Suhara (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The rapid integration of Artificial Intelligence (AI) into workplaces presents both opportunities and challenges for organizations, particularly in managing human capital. Drawing on Human Capital Theory and the Technology Acceptance Model (TAM), this study investigates how organizations address AI-related challenges such as skill gaps, employee resistance, and job displacement concerns. The research aims to identify effective strategies for enhancing workforce readiness and adaptability in the AI era. Using a qualitative approach, in-depth interviews were conducted with 18 respondents from diverse industries, complemented by statistical analysis to examine correlations between training frequency and AI implementation success. The findings reveal that digital and social skills training, fostering an innovation-supportive culture, and involving workers in technological transitions are critical to effective adaptation. Statistical results indicate a significant positive correlation between the frequency of digital skills training and AI integration success. This study contributes to the literature by integrating technical and social competencies into a unified human capital strategy framework, offering actionable guidance for organizations navigating AI-driven transformation. The results provide theoretical and practical implications for policy design to support sustainable workforce development in the context of automation and AI adoption.